Effects of Atmospheric CO2 Enrichment on Soil CO2 Efflux in a Young Longleaf Pine System - G. Brett Runion; J. R. Butnor; S. A. Prior; R. J. Mitchell; H. H. Rogers (International Journal of Agronomy)
The southeastern landscape is composed of agricultural and forest systems that can store carbon (C) in standing biomass and soil. Research is needed to quantify the effects of elevated atmospheric carbon dioxide (CO2) on terrestrial C dynamics including CO2 release back to the atmosphere and soil sequestration. Longleaf pine savannahs are an ecologically and economically important, yet understudied, component of the southeastern landscape. We investigated the effects of ambient and elevated CO2 on soil CO2 efflux in a young longleaf pine system using a continuous monitoring system. A significant increase (26.5%) in soil CO2 efflux across 90 days was observed under elevated CO2; this occurred for all weekly and daily averages except for two days when soil temperature was the lowest. Soil CO2 efflux was positively correlated with soil temperature with a trend towards increased efflux response to temperature under elevated CO2. Efflux was negatively correlated with soil moisture and was best represented using a quadratic relationship. Soil CO2 efflux was not correlated with root biomass. Our data indicate that, while elevated CO2 will increase feedback of CO2 to the atmosphere via soil efflux, terrestrial ecosystems will remain potential sinks for atmospheric CO2 due to greater biomass production and increased soil C sequestration.